Estimación de los contenidos de carbono en un área de restauración pasiva de bosque montano de la reserva "El Cristal" cantón y provincia de Loja - Chavez Campos, Jorge Luis (2024)
The montane forests have a great biodiversity of flora and fauna, despite their biological importance they are affected by deforestation and forest fires, where the main driver is the change and use of soil for agricultural purposes. The result of this originates the formation of secundary forests, which are part of the ecological restoration procedures, influencing the recovery of ecosystem services such as carbon storage. In this context, the present study aims to estimate the carbon content in the aerial biomass and necromass in passive restoration areas of montane forest in the “El Cristal” reserve. To assess the carbon stored in the aboveground biomass, four permanent plots of 50 × 50 m were established, divided into 4 subplots of 25 × 25 m; based on (DBH >5 cm) at 1.30 cm, total height (Ht) and wood density obtained from the Wood Density Database. To estimate aboveground biomass the equation of Chave et al, (2014) was used, for carbon calculation the biomass was multiplied by the conversion factor 0.47. To estimate the carbon stored in the necromass, it was classified into three subcomponents: litter, standing dead trees and fallen dead wood. For leaf litter, 1 × 1 m subplots were installed, all dead material within the subplot was weighed, and 300 g were collected to estimate the carbon content. For coarse dead wood, carbon was estimated from standing dead trees > 10 cm DBH and fallen dead wood with diameters > 10 cm in each of the 25 × 25 m subplots. The results obtained from this study show that the passive restoration area captures an average of 40.00 tC/ha, where 78% belongs to aerial biomass (31.30 tC/ha) and 22% to necromass (8.68 tC/ha). The species with the highest carbon content are: Alnus acuminta and Myrsine sodiroana. As a conclusion, the passive restoration area stores 41.43 % (40.00 tC/ha) of carbon content in relation to the montane Andean evergreen forest (96.53 tC/ha), which proves that the passive restoration strategy is primordial for the long-term recovery of ecosystem services, particularly for carbon content at the landscape level.